The Mobilities of Carriers Confined in a Single-side Doped Square Quantum Wells Dependence on Temperature - Hai, Tran Thi (VNU Journal of Science: Mathematics - Physics, 2017)
A theory is given of the mobility of a two-dimensional electron gas at high temperature in single-side square quantum wells. Within the variational approach, we obtain analytic expressions for the carrier distribution, and autocorrelation functions for various scattering mechanisms. We examine the dependence of the mobilities of carriers on the temperature. Our theory is able to well reproduce the recent experimental data on transport in 1S-doped square QWs, e.g., acoustic-phonon partial mobility dependence on temperature for single-side modulation doped square quantum wells.